Hyperhomocysteinemia-induced death of retinal ganglion cells: The role of Müller glial cells and NRF2 - Navneet, Soumya (Redox Biol, 2019)
Hyperhomocysteinemia (Hhcy), or increased levels of the excitatory amino acid homocysteine (Hcy), is implicated in glaucoma, a disease characterized by increased oxidative stress and loss of retinal ganglion cells (RGCs). Whether Hhcy is causative or merely a biomarker for RGC loss in glaucoma is unknown. Here we analyzed the role of NRF2, a master regulator of the antioxidant response, in Hhcy-induced RGC death in vivo and in vitro. By crossing Nrf2(−/−) mice and two mouse models of chronic Hhcy (Cbs(+/-) and Mthfr(+/-) mice), we generated Cbs(+/-)Nrf2(−/−) and Mthfr(+/-)Nrf2(−/−) mice and performed systematic analysis of retinal architecture and visual acuity followed by assessment of retinal morphometry and gliosis. We observed significant reduction of inner retinal layer thickness and reduced visual acuity in Hhcy mice lacking NRF2. These functional deficits were accompanied by fewer RGCs and increased gliosis. Given the key role of Müller glial cells in maintaining RGCs, we established an ex-vivo indirect co-culture system using primary RGCs and Müller cells. Hhcy-exposure decreased RGC viability, which was abrogated when cells were indirectly cultured with wildtype (WT) Müller cells, but not with Nrf2(−/−) Müller cells. Exposure of WT Müller cells to Hhcy yielded a robust mitochondrial and glycolytic response, which was not observed in Nrf2(−/−) Müller cells. Taken together, the in vivo and in vitro data suggest that deleterious effects of Hhcy on RGCs are likely dependent upon the health of retinal glial cells and the availability of an intact retinal antioxidant response mechanism.